LOCAL CONTENT ADIWIYATA CURRICULUM AND RESPONSIVE WEB-BASED MITIGATION - R, Rika Kurnia; Sumadi, Tjipto; Yufiarti, Yufiarti (Unnes Science Education Journal, 2019)
This research is conducted to fill the absence of guidance on Adiwiyata curriculum based on local wisdom and mitigation through the integration of material into the syllabus and lesson plans implementation in elementary schools. It aims to produce an elementary curriculum that can be accessed through responsive web as an effort to realize schools that responsible for environmental management and protection and also know how to mitigate disasters. The type of this research is model development using ADDIE model. Sample of respondents are first and second grade teachers, while subjects of trial are 30 students of SD Negeri 5 Palu City. Data are taken from observations, interviews, and questionnaires with the instruments of validation sheets, response questionnaires, and environmental care instruments. The research results show that: 1) curriculum validation of content and product appearance is in the good category, 2) the guidance is practical and effective to use, and 3) it is useful for realizing environmental care and introducing regional culture and art. The development of this curriculum is feasible and can increase the environmental awareness by utilizing natural materials and waste as learning media.